Isolation of a TMTAA‐Based Radical in Uranium bis‐TMTAA Complexes. (8th November 2018) - Hohloch, Stephan; Garner, Mary E.; Booth, Corwin H.; Lukens, Wayne W.; Gould, Colin A.; Lussier, Daniel J.; Maron, Laurent; Arnold, John
Abstract: We report the synthesis, characterization, and electronic structure studies of a series of thorium(IV) and uranium(IV) bis‐tetramethyltetraazaannulene complexes. These sandwich complexes show remarkable stability towards air and moisture, even at elevated temperatures. Electrochemical studies show the uranium complex to be stable in three different oxidation states; isolation of the oxidized species reveals a rare case of a non‐innocent tetramethyltetraazaannulene (TMTAA) ligand.